Physical Dating Violence Victimization among LGBTQ Youth: Disclosure and Association with Mental Health - Price, Myeshia N. (Journal of interpersonal violence, 2023)
Youth dating violence and youth suicide are both major public health concerns. However, little research examines the intersection of these issues among lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQ) youth. The current study examined the association between physical dating violence victimization and mental health using online survey data collected from 39,126 LGBTQ youth of ages 13 to 24 in the United States. Overall, 11% of LGBTQ youth who were in a relationship in the past year experienced physical dating violence victimization, with 4% having experienced it once and 7% having experienced it multiple times. Rates of experiencing physical dating violence victimization varied based on a number of youth characteristics and environmental factors. Past-year physical dating violence victimization was associated with nearly four times the odds of attempting suicide in the past year. Given the intersection of suicide risk and dating violence among LGBTQ youth, dating violence prevention organizations must be LGBTQ-inclusive, and suicide prevention must be equipped to address dating violence victimization. The higher rates of physical dating violence victimization among multiple marginalized and socioeconomically disadvantaged LGBTQ youth suggest the need for an intersectional approach that addresses the structural factors that place LGBTQ youth at risk for physical dating violence.